(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
This study was carried out to highlight the probable causes and factors related to maternal mor tality and morbidity in criminal abortion cases. 100 cases of criminal abortion were referred to SRN Hospital MLN Medical College Allahabad since July 2009 June 2010 were studied. Out of them 9 were died because of various complications (mortality rate-9%). Young adolescent married of low socioeconomic illiterate women came from rural areas received criminal abortion services by unskilled personnel significantly associated with maternal mortality and morbidity. Education and encouragement of safe sex practices, reproductive health knowledge to adoles cent & illiterate women, access to contraception adoption of modern methods of termination of pregnancy with prophylactic antibiotic use, additional training of physicians and other health workers in abortion care to reduce complications of criminal abortion.